The Role Peran Badan Pengawas Pemilihan Umum (BAWASLU) Dalam Mengatasi dan Menindak Pelanggaran Pemilihan Umum: Tinjauan Hukum dan Praktik: The Role of the General Election Supervisory Body (BAWASLU) in Overcoming and Taking Action against General Election Violations: A Review of Law and Practice - Okvita Sekar Fadhilah (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2024)
This article aims to explain the role of the Election Supervisory Body (Bawaslu) in overcoming and cracking down on election violations with a comprehensive approach from a legal perspective and field practice. First, from a legal perspective, this article analyzes the role of Bawaslu in dealing with election violations in accordance with the legal framework that regulates them. Second, from a field practice perspective, this article evaluates how Bawaslu carries out its role in cracking down on election violations through field observations and case studies. Furthermore, this article identifies the obstacles or challenges faced by Bawaslu in carrying out its role, including institutional, political and technical obstacles. Finally, the effectiveness of the efforts made by Bawaslu in overcoming and cracking down on election violations is evaluated both from a legal perspective and field practice to conclude about the success and expansion of the strategy needed. By combining legal review and field practice, this article provides comprehensive insight into Bawaslu's role in ensuring election integrity and strengthening democracy.